Genetic parameters, prediction, and selection in a white guinea yam early-generation breeding population using pedigree information (2020)
Better understanding of the genetic control of traits in breeding populations is crucial for the selection of superior varieties and parents. This study aimed to assess genetic parameters and breeding values for six essential traits in a white Guinea yam (Dioscorea rotundata Poir.) breeding population. For this, pedigree-based best linear unbiased prediction (P-BLUP) was used. The results revealed significant nonadditive genetic variances and medium to high (.45–.79) broad-sense heritability estimates for the traits studied. The pattern of associations among the genetic values of the traits suggests that selection based on a multiple-trait selection index has potential for identifying superior breeding lines. Parental breeding values predicted using progeny performance identified 13 clones with high genetic potential for simultaneous improvement of the measured traits in the yam breeding program. Subsets of progeny were identified for intermating or further variety testing based on additive genetic and total genetic values. Selection of the top 5% progenies based on the multi-trait index revealed positive genetic gains for fresh tuber yield (t ha−1), tuber yield (kg plant−1), and average tuber weight (kg). However, genetic gain was negative for tuber dry matter content and Yam mosaic virus resistance in comparison with standard varieties. Our results show the relevance of P-BLUP for the selection of superior parental clones and progenies with higher breeding values for interbreeding and higher genotypic value for variety development in yam.